2002
DOI: 10.1126/science.1075159
|View full text |Cite
|
Sign up to set email alerts
|

Climate Effects of Black Carbon Aerosols in China and India

Abstract: In recent decades, there has been a tendency toward increased summer floods in south China, increased drought in north China, and moderate cooling in China and India while most of the world has been warming. We used a global climate model to investigate possible aerosol contributions to these trends. We found precipitation and temperature changes in the model that were comparable to those observed if the aerosols included a large proportion of absorbing black carbon ("soot"), similar to observed amounts. Absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
1,340
8
15

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,970 publications
(1,406 citation statements)
references
References 23 publications
43
1,340
8
15
Order By: Relevance
“…The Indian Ocean and monsoon exhibit a coupled relationship 32,42,43 , and it is also possible that a feedback from a weak monsoon accelerates the warming in the Indian Ocean 22 . Some studies have suggested a role for anthropogenic aerosols in weakening the monsoon circulation during the recent decades 40,[44][45][46][47][48] . It is possible that such a weakened circulation amplifies the SST warming due to a decreased evaporation.…”
Section: Discussionmentioning
confidence: 99%
“…The Indian Ocean and monsoon exhibit a coupled relationship 32,42,43 , and it is also possible that a feedback from a weak monsoon accelerates the warming in the Indian Ocean 22 . Some studies have suggested a role for anthropogenic aerosols in weakening the monsoon circulation during the recent decades 40,[44][45][46][47][48] . It is possible that such a weakened circulation amplifies the SST warming due to a decreased evaporation.…”
Section: Discussionmentioning
confidence: 99%
“…The various effects that particles have on the atmosphere and clouds in a region may result in regional climate changes. For instance, Menon et al suggest that the observed trend toward increased summer floods in southern China and drought in the north may be linked to absorbing particles that alter the regional atmospheric circulation and contribute to regional climate change (22). Finally, climate change and air quality are linked through the chemistry of the atmosphere, as some air pollutants influence the lifetimes of GHGs.…”
Section: Climate-change and Air-pollution Linksmentioning
confidence: 99%
“…Atmospheric particles have an influence on the global climate system, providing an adverse effect on human health and visibility (Huebert et al, 2003;Kaufman et al, 2002;Menon et al, 2002;Richter et al, 2005). Severe droughts in northern China and enhanced summer floods in southern China may be associated with the anthropogenic atmospheric particles that modify the regional air circulation (Menon et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Severe droughts in northern China and enhanced summer floods in southern China may be associated with the anthropogenic atmospheric particles that modify the regional air circulation (Menon et al, 2002). Dicarboxylic acids are ubiquitously present in atmospheric aerosols and they are in general the dominant class of organic components.…”
Section: Introductionmentioning
confidence: 99%